ADAPTATION TO CHANGES ON THE JOB MARKET - THE ROLE OF CAREER COUNSELING FOR STUDENTS - Kukla, Daniel Mariusz (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Professional counseling for students plays an important role and support for students in the transition process from education to the labor market. However, in order to be effective, the content of consultancy services should be adapted to the real needs of students (often resulting from transformations in the education and work market). This study indicates selected challenges faced by contemporary students (future graduates) in the context of the dynamics of the labor market development but also adaptation to permanent changes in this market.